File And Pc-Based CNC Controller Using Integrated Interface System (I2S) - Mohamed, Saiful Bahri; Tengku Sulaiman, Tengku Mohd Sharir; Minhat, Mohamad; Mohamed, Ahmad Syafiq; Mohamed, Ahmad Ridhuan; Yusof, Siti Nurul Akmal (Penerbit Akademia Baru, 2020)
STEP file is known as a CAD neutral file which stands for Standard for the Exchange of Product model data for the next generation of data model between CAD/CAM and CNC system. It contains three-dimensional data in ISO 10303-21 format which ultimately all CNC programs can recognize. Now however, not all documents in the STEP file are appropriate for programming CNC G-Code. This paper explicates the design, development and testing of an Integrated Interface System (I2S) using knowledge discovery approach. The objective of this study is to provide helps for understanding the STEP-NC machining operation protocol. The system provides function of reading and extracting applicable data related with the machining functions from STEP file, that eventually write file format Geometrical Code (G-Code – ISO 6983) as an output file. G-Code is known as one of the low-level programming languages in CNC system. The sample of machined block designs from 3D CAD modeler where the features need to be machined from a blank workpiece and saved in the STEP neutral file format. In this work, the simulation in the Mach3 software and physical machining using 3-axis CNC milling machine installed with PC-based CNC controller has been validated.